1992
DOI: 10.1002/gcc.2870050304
|View full text |Cite
|
Sign up to set email alerts
|

Non‐random abnormalities of chromosomes 3, 6, and 8 associated with posterior uveal melanoma

Abstract: We present ten cases of posterior uveal melanoma which were karyotyped after short-term culture. One tumour had a normal chromosome complement. The remaining nine tumours were cytogenetically abnormal, with chromosomes 3, 6, 8, 11, and 13 most frequently involved. Abnormalities of chromosome 13 were seen in two cases, chromosome 11 in three cases, and chromosomes 3, 6, and 8 in five cases. Four tumours, all derived from the ciliary body, demonstrated monosomy 3 and i(8q), confirming the involvement of these ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…This reflects the greater sensitivity of array CGH. Previous reports have stated that the most frequent anomaly in UVM is loss of an entire copy of chromosome 3 (Sisley et al, 1992;Wiltshire et al, 1993;White et al, 1998). In our analysis, however, the most common chromosomal changes identified were 8q gains (14/18; 78, 95% confidence interval: 52 -94%), 6p gains (12/18; 78, 95% confidence interval: 41 -87%), and monosomy 3 (10/18; 56, 95% confidence interval: 31 -78%).…”
Section: Resultsmentioning
confidence: 99%
“…This reflects the greater sensitivity of array CGH. Previous reports have stated that the most frequent anomaly in UVM is loss of an entire copy of chromosome 3 (Sisley et al, 1992;Wiltshire et al, 1993;White et al, 1998). In our analysis, however, the most common chromosomal changes identified were 8q gains (14/18; 78, 95% confidence interval: 52 -94%), 6p gains (12/18; 78, 95% confidence interval: 41 -87%), and monosomy 3 (10/18; 56, 95% confidence interval: 31 -78%).…”
Section: Resultsmentioning
confidence: 99%
“…Cases Som 10,11,17,22,30 and 35 were presented in Sisley et al (1990), cases Som 36,37,47,52,53,57,59,60,61,62 and 63, were detailed in Sisley et al (1992) and cases Som 95 and 140 reported in Tappin et al (1996). The significance of chromosome 3 and 8 abnormalities in the series of 42 patients has been considered separately (Sisley et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…9 A major breakthrough was the observation that many uveal melanomas lack one copy of chromosome 3, and that these monosomic tumours are usually those that metastatise. 29,30 Simple determination of monosomy 3 is inaccurate, however, because the chromosomal defect can be masked by: (1) duplication of the remaining copy to produce isodisomy (both chromosomes then derive from the same parent); (2) partial chromosomal deletion, which can be missed by some methods; and (3) modulation of the risk of metastasis by other choromsomal errors, such as 6p gain and 8q gain. [31][32][33] At present, the method of choice for initial chromosomal analysis is multiple ligation probe amplification (MLPA), which probes multiple loci across several chromosomes.…”
Section: Prognosis Of the Primary Tumourmentioning
confidence: 99%